Relationship Between Systemic Lupus Activity Measurement (SLAM) Score and Mortality in Systemic Lupus Erytemathosus (SLE) Inpatients - Ayu Paramaiswari; Nyoman Kertia; Deddy Wachid Achadiyono (Faculty of Medicine Universitas Gadjah Mada, 2014)
ABSTRACTBackground: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disorder that can be severe and life threatening. Mortality in SLE may due to lupus activity or long-term sequel. Systemic Lupus Activity Measurement (SLAM) score is a tool that can count lupus disease activity inpatients.Aims: To analyze the relationship between SLAM score and mortality in lupus inpatients.Methods: Retrospective cohort study used for reaching objective of the study. Lupus inpatients was used as research population. Medical record was used as study data collection over periods of 2006 until 2011. Independent variable was a SLAM score. The cut point of SLAM score was made based on the mean of SLAM score (16.7 point score). Dependent variable was mortality.Results: There were differences between number of ACR criteria fi ndings, pneumonia, heart rate with SLAM score (p value 0.001; 0.001; 0.002 respectively).There was a difference of median survival between less and more than 16.7 point score, 45 and 28 respectively (p 0.034). There was a relationship between SLAM score (more than 16.7 point score) and mortality HR 2.78 (96% CI 1.01-7.53). There was a difference of mortality incidence between more and less than 16.7 point score, 0.35 and 0.10 respectively. There was a relationship between SLAM score (more than 16.7 point score) and mortality RR 3.5 (95% CI). Mortality in lupus inpatients was 23%.Conclusion: There was a relationship between SLAM score and mortality on lupus inpatients.Keywords: SLE, SLAM, Mortality